The angiotensin‐converting enzyme gene insertion/deletion polymorphism in Indian patients with vitiligo: a case–control study and meta‐analysis. (5th June 2013) - Patwardhan, M.; Pradhan, V.; Taylor, L.H.; Thakkar, V.; Kharkar, V.; Khopkar, U.; Ghosh, K.; Gawkrodger, D.J.; Teare, M.D.; Weetman, A.P.; Kemp, E.H.
Summary Background Vitiligo is a common, acquired, idiopathic depigmenting skin disorder. Although the exact pathogenesis remains unknown, genetic susceptibility and autoimmune responses play a role in vitiligo development. Previous studies have suggested that the D allele of the insertion/deletion (I/D) polymorphism of the angiotensin‐converting enzyme (ACE) gene is associated with vitiligo in Indians and Koreans. Furthermore, significantly higher serum ACE levels have been demonstrated in patients with some autoimmune and autoinflammatory disorders. Objectives The objectives were to investigate any association between the ACE I/D polymorphism and vitiligo susceptibility in an Indian population, and to compare serum ACE levels in patients with vitiligo and healthy subjects. Methods The ACE I/D genotypes of 79 patients with vitiligo and 100 normal individuals were determined by polymerase chain reaction amplification. A meta‐analysis was done to compare the distribution of the ACE I/D alleles and genotypes in the current and three previous studies. Serum ACE levels were evaluated by enzyme‐linked immunosorbent assay. Results A significant increase in the frequency of the ACE I/D D allele was evident in patients with vitiligo in both the case–control study [P = 0·005; odds ratio (OR) 1·87; 95% confidence intervals (CI) 1·22–2·85] and the meta‐analysis (P = 0·044; OR 1·44; 95% CI 1·01–2·06). Serum ACE levels were significantly increased in patients with vitiligo compared with healthy subjects (P < 0·0001). Conclusions In agreement with earlier reports, the ACE I/D D allele is associated with vitiligo susceptibility in the Indian population. The significantly elevated serum ACE levels in our cohort of patients with vitiligo concur with those previously found in patients with some other autoimmune diseases.